Insomnia and its Ayurveda Management– A Critical Review. - Irshad, Nazia; Singh, N R; Varsakiya, Jitendra (International Research Journal of Ayurveda & Yoga, 2023)
Sleep is one of the basic and vital necessities of the body. Sleep is a normal biological process that provides the body (Sharir) and intellect (Mann) enough rest. Because of this, Ayurveda emphasises the importance of sleep, referring to it as Trayoupasthambh (Ahara-dietary habits, Nidra-sleep pattern, and Brahrnacharya-celibacy), (three support pillars). According to the text, Dhatu Samyata (the balance of the body constituents) depends on sleep. Particularly, the state of one’s food and sleep affects obesity and emaciation. A careful review of the Ayurvedic medical literature reveals that increased Vata, old age, habit, and indulgence in work are the main causes of the Anidra (sleeplessness). This condition is also a consequence of a variety of diseases, and a number of ailments are caused and aggravated by inadequate sleep. In Ayurvedic literature, terms for insomnia include Anidra, Nidranasha, and Asvapna. Insomnia is a sleep disorder where people experience difficulty in sleeping or inadequate, poor-quality sleep. They may have trouble falling asleep, waking up frequently during the night with difficulty returning to sleep, and waking up too early in the morning. However, insufficient sleep increases the risk of numerous lifestyle-related diseases and impairs working capacity and concentration. Therefore the current article discusses the causes, effects, and treatment options for insomnia from an Ayurvedic perspective.